Peri-urban agricultural expansion and forest loss in lapite, Ibadan, its implication for floristic composition and species invasion (2023)
Peri-urban agriculture in developing countries is in increasing demand for food as a result of increasing population. It offers an alternative land-use for income generation to ameliorate urban poverty and contributing to global food security. Peri-urban agriculture however causes forest loss, degradation, and species invasion. This study investigated the extent of forest loss, species composition, and importance of invasive species in peri-urban agriculture at Moniya, Akinyele local government area, Ibadan, Oyo State in the wet season of 2019. The study site was located at Lapite, Moniya, Ibadan on N 07° 34.253, E 003° 54.633; 235 m above sea level. Ten farmlands (sizes: 1120 m2 and 3750 m2) were evaluated within 70.4 hectares. Systematic sampling for herbaceous and woody flora was conducted using plot sizes of 10 × 10 m and one square meter quadrats, respectively. Land-use cover change from 1998-2018 was assessed with Arc GIS 10 on USGS Landsat imageries. Enumerated floristic data were analyzed for species composition, relative important value (RIV), and invasive species were noted. One hundred and thirty-two (132) herbaceous species in 38 families were enumerated with RIV ranging from 0.02% - 13.9%. Talinum fruticosum had the highest RIV (13.58%). Twenty woody species in 13 families were enumerated with RIV of 1.33% to 23.2%. Elias guineensis had the highest RIV. Five invasive species were identified. Leucaena leucocephala had the highest occurrence among invasive woody species (RIV=13.38). Alternanthera sessilis was the most (RIV= 2.5%) occurring invasive species. GIS analysis indicated bare/deforested areas increased from 8.33% in 1998 to 46.23% in 2018. Loss of cover and species invasion was attributed to the expansion of agricultural areas and might increase the impact of climate change in the area. Peri-urban agricultural activities in Moniya should be regulated to prevent the further incursion of invasive species and forest loss with associated benefits.